Understanding the system dynamics of obesity-related behaviours in 10- to 14-year-old adolescents in Amsterdam from a multi-actor perspective - Luna Pinzon, Angie; Stronks, Karien; Emke, Helga; van den Eynde, Emma; Altenburg, Teatske; Dijkstra, S. Coosje; Renders, Carry M.; Hermans, Roel; Busch, Vincent; Chinapaw, Mai J. M.; Kremers, Stef P. J.; Waterlander, Wilma (Frontiers in Public Health, 2023)
Introduction and Methods To develop an understanding of the dynamics driving obesity-related behaviours in adolescents, we conducted systems-based analysis on a causal loop diagram (CLD) created from a multi-actor perspective, including academic researchers, adolescents and local stakeholders. Results The CLD contained 121 factors and 31 feedback loops. We identified six subsystems with their goals: (1) interaction between adolescents and the food environment, with profit maximisation as goal, (2) interaction between adolescents and the physical activity environment, with utility maximisation of outdoor spaces as goal, (3) interaction between adolescents and the online environment, with profit maximisation from technology use as goal, (4) interaction between adolescents, parenting and the wider socioeconomic environment, with a goal focused on individual parental responsibility, (5) interaction between healthcare professionals and families, with the goal resulting in treating obesity as an isolated problem, and (6) transition from childhood to adolescence, with the goal centring around adolescents’ susceptibility to an environment that stimulates obesity-related behaviours. Discussion Analysis showed that inclusion of the researchers’ and stakeholders’ perspectives contributed to an understanding of how the system structure of an environment works. Integration of the adolescents’ perspective enriched insights on how adolescents interact with that environment. The analysis further showed that the dynamics driving obesity-related behaviours are geared towards further reinforcing such behaviours.